2010
DOI: 10.1002/ceat.201000105
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Production with Stirred‐Media Mills: Opportunities and Limits

Abstract: Nanoparticles can be produced by wet grinding in stirred‐media mills. In the lower nanometer range a true grinding limit exists, where the transferred energy from the grinding media is no longer sufficient to induce further breakage of the particles even after stressing events with high stress energies. Variations in process conditions lead to the conclusion that the grinding limit is hardly affected by most of the investigated process parameters. However, at high solids concentrations and/or small particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…However, the real grinding media velocities are definitely smaller than the tip speed used for the calculation of SE and thus, according to Stender et al, the mean stress energy is about two to three magnitudes lower than the maximum possible stress energy [25]. Moreover, a further reduction in stress energy can occur if the grinding media collisions are damped by higher suspension viscosities [31]. Hence, the measured bursting energy lies well in the range of the probable mean stress energy of the stirredmedia mill.…”
Section: Macromechanical Characteristicsmentioning
confidence: 95%
“…However, the real grinding media velocities are definitely smaller than the tip speed used for the calculation of SE and thus, according to Stender et al, the mean stress energy is about two to three magnitudes lower than the maximum possible stress energy [25]. Moreover, a further reduction in stress energy can occur if the grinding media collisions are damped by higher suspension viscosities [31]. Hence, the measured bursting energy lies well in the range of the probable mean stress energy of the stirredmedia mill.…”
Section: Macromechanical Characteristicsmentioning
confidence: 95%
“…The efficiency of solvent viscosity in reducing SI can be estimated by introducing an energy transfer coefficient  r . Knieke et al [51] derived an expression for  r by adapting the model of Davis et al [77], which describes the collision of spheres in a viscous medium, to the milling bead motion. The dimensionless  r represents the viscous energy transfer when a particle is captured between two beads and is defined by (10) where x is the particle size, d bead is the bead diameter, and St bead is the Stokes number of the beads, which is defined by…”
Section: Influence Of Delamination Process Parameters On Product Yielmentioning
confidence: 99%
“…Stirred-media milling is a simple, effective, and very scalable top-down method for the production of submicron and nanoparticles, e.g., glasses, crystalline materials, inorganic, organic, and polymer particles, [4753]. In 2010, Knieke et al [51] showed that graphite delamination in stirred-media mills is a promising way to produce graphene (see also Yao et al [54] and Zhao et al [55,56]). Salt-assisted dry milling of graphite in planetary ball mills has also been used for graphene production, but long processing times (24 h) are required [57,58].…”
Section: Introductionmentioning
confidence: 98%
“…Due to the fast and efficient micronization even at high solid content, stirred media milling is often the method of choice in product engineering of particles in the submicron and nanometer size range for a wide variety of materials. So far, the majority of studies related to stirred media milling have been done for inorganic feed materials [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%